Vulnerability, poverty and coping in Zimbabwe - Kate Bird; Martin Prowse (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper uses five life histories from three locations in Zimbabwe - one peri-urban, one urban and one rural to provide a window on current processes of impoverishment and adverse coping. Each case and location highlight key aspects of Zimbabwe's recent economic and political turmoil. Together the cases suggest that, similar to Hoddinott's work on the persistence of the 1993-94 rainfall shock in rural Zimbabwe, above and beyond increased mortality rates and morbidity levels, current adverse forms of coping are creating widespread irreversible wellbeing losses. The persistent effects of the current crisis surely adds weight to arguments that the international community should be more, rather than less, proactive in delivering aid to the Zimbabwean people, despite the politicization of aid and logistical difficulties.
Keywords: O2; 330; Zimbabwe; fragile states; fragile groups; vulnerability; coping strategies; life histories; land reform; labour markets; HIV; state repression; urban poverty; input and output markets; Armut; Simbabwe